Comparison of different excitation modes for the analysis of light elements with a TXRF vacuum chamber. Issue 2 (22nd May 2015) - Prost, J.; Wobrauschek, P.; Streli, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this work was to compare different excitation modes for the analysis of light elements from carbon (Z = 6) upwards using a total reflection X-ray fluorescence analysis (TXRF) vacuum chamber which allows the attachment of different X-ray tubes and detectors. In the first set of experiments, two water-cooled high-power X-ray tubes with Cr (Z = 25) and Cu (Z = 29) anodes, respectively, were compared with an air-cooled low-power tube with Mo anode (Z = 42) and a thin Be window for the transmission of Mo-L lines. In the first two cases, monochromatic Kα radiation was used for excitation, while in the case of the Mo tube the multilayer acted as a cut-off reflector and part of the Mo bremsstrahlung continuum together with the Mo-L series were used for excitation. Multi-element standards containing elements ranging from Na (Z = 11) to Ti (Z = 22) were analyzed by a silicon drift detector (SDD) with a 300 nm ultrathin polymer window (UTW). Detection limits were calculated and compared for the three excitation modes. The second set of experiments was performed using an air-cooled low-power X-ray tube with Rh anode (Z = 45) in order to show that a conventional SDD with a 25 μm beryllium window can be used for the detection of elements from Na upwards. The use of compact air-cooled low-power X-ray tubes together with Peltier-cooled SDDs with UTW should lead to the development of highly sensitive tabletop vacuum TXRF spectrometers with a design optimized for the analysis of light elements. Detection limits as achieved by vacuum chambers using conventional water-cooled high-power tubes (e.g. Streli et al., 2004) are realistically achievable with the new approach.